PENYULUHAN KESEHATAN GIGI DAN MULUT DI TK SATU ATAP SD N MARGAKAYA KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN TAHUN 2017 - Dessy Hermawan; Linawati Novikasari; Yustinus Windartono (Universitas Malahayati Lampung, 2018)
ABSTRACT One od preventive way to prevent dental growth disorders in children is going to dentist every 6 months. Giving dental health education to parents who have children aged 5-9 years is very important because in this is a critical period, period of growth and development, especially the period of permanent dentition, this is done so that dental caries in children does not occur. Objectives of this activities are increasing knowledge of parents in Trans Tanjungan village about Dental and Oral health. The activities are education using leaflets and demonstrations. Education can increase parents knowledge about caring dental and oral health.